The Conservative Revolution in the Weimar Republic. Definition, origins and member groups - Ortega Esquembre, César (Revista de Filosofía, 2025)
The aim of this paper is to offer a reconstruction of the so-called conservative revolution of the Weimar Republic. The work is divided into three sections. I first offer a schematic history of European conservative political thought, by distinguishing four of its most important phases. In the second section I discuss some of the intellectual origins of the conservative revolution. Finally, I reconstruct the five groups in which this movement can be divided: the Völkisch, the Jungkonservativen or young conservatives, the Nationalrevolutionäre or national revolutionaries, the Bündischen or youth leagues, and the Landvolkbewegung or peasant movement.